The ability of rheumatologists blinded to prior workup to diagnose rheumatoid arthritis only by clinical assessment: a cross-sectional study. (29th May 2018) - Ehrenstein, Boris; Pongratz, Georg; Fleck, Martin; Hartung, Wolfgang
Abstract: Objectives: We aimed to study the ability of board-certified rheumatologists, blinded to all prior diagnostic test results, to establish the presence/absence of an inflammatory rheumatic disease (IRD) or RA among polyarthralgia or arthritis patients, solely relying on clinical assessment. Methods: We performed a prospective, examiner-blinded, cross-sectional study documenting the diagnostic work in four sequential steps (medical history, physical examination, musculoskeletal ultrasonography and laboratory tests) of board-certified rheumatologists in a convenience cohort of 100 patients referred for inpatient diagnostic workup to a tertiary care rheumatology centre. Results: The ability to correctly identify patients with or without an IRD (diagnostic accuracy) increased from 27% after the clinical assessment to 53% after the ultrasonography and to 70% after taking laboratory test results into account. The corresponding values for correctly identifying patients with or without RA were 19, 42 and 60%, respectively. Therefore the diagnostic accuracy of solely clinical assessment for determining the diagnosis of IRD or RA compared with the diagnosis established by a consecutive thorough in-patient workup was only 27 and 19% in our cohort, respectively. Pretreatment with corticosteroids (in the prior 7 days) vs none did not alter these results substantially (20 vs 29% for IRD, 15% vs 20% for RA). Conclusion: Experienced rheumatologists, if deprived of information on prior external imaging and laboratory workup by blinding, were not able to correctly classify the majority of patients presenting with polyarthralgia or arthritis symptoms for inpatient workup, relying only on a brief symptom-focused medical history and physical examination.